The Positive Power of Hedgehog Leadership in Academe - Thomas N. Duening (Academic Chairpersons Conference Proceedings, 2017)
This workshop will focus on helping academic chairs become more hedgehog-like in their leadership style and faculty interactions. The research streams that inform this session include positive psychology, positive organization behavior, and affective neuroscience. The expected outcome for participants is an enhanced ability to create an environment of opportunity for their faculty. The session leader has been using this approach as chair of the management department for nearly two years. As an example of the power of hedgehog leadership one faculty member in management last year received the college’s outstanding faculty member aware for the first time in 26 years!
Keywords: Leadership; pragmatism; effectuation; virtues